VD_FINDINFO Jug / 2009 / 29 vom 15. Mai 2009 - VD Tribunal cantonal (2009)
ACTION RÉVOCATOIRELP, RESTITUTIONEN GÉNÉRAL, RÉGIME MATRIMONIAL, SÛRETÉS, SURENDETTEMENT | 193 CC, 203 al. 2 CC, 250 al. 2 CC, 83 CO, 74 LOJV, 115 al. 2 LP, 285 LP, 286 LP, 287 LP, 288 LP, 289 LP, 290 LP, 291 LP, 42 LVLP